2020
DOI: 10.1038/s41598-020-71707-2
|View full text |Cite
|
Sign up to set email alerts
|

Wavelength of light and photophobia in inherited retinal dystrophy

Abstract: Inherited retinal dystrophy (IRD) patients often experience photophobia. However, its mechanism has not been elucidated. This study aimed to investigate the main wavelength of light causing photophobia in IRD and difference among patients with different phenotypes. Forty-seven retinitis pigmentosa (RP) and 22 cone-rod dystrophy (CRD) patients were prospectively recruited. We designed two tinted glasses: short wavelength filtering (SWF) glasses and middle wavelength filtering (MWF) glasses. We classified photop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…It is challenging to speculate how these findings translate into clinical settings, because of the lack of corresponding data from RP patients. Hypersensitivity to bright light (called by the debated misnomer “photophobia”) is common in RP ( Hamel, 2006 ; Otsuka et al, 2020 ), and could in part result from similar hyperexcitation of the primary visual tract as observed in RP model mice. The relatively well-maintained behavioral vision of Rho P23H/WT mice may also be reflected in clinical settings, as many RP patients show minimal disturbances in subjective vision even at an advanced disease stage ( Hartong et al, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is challenging to speculate how these findings translate into clinical settings, because of the lack of corresponding data from RP patients. Hypersensitivity to bright light (called by the debated misnomer “photophobia”) is common in RP ( Hamel, 2006 ; Otsuka et al, 2020 ), and could in part result from similar hyperexcitation of the primary visual tract as observed in RP model mice. The relatively well-maintained behavioral vision of Rho P23H/WT mice may also be reflected in clinical settings, as many RP patients show minimal disturbances in subjective vision even at an advanced disease stage ( Hartong et al, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some patients (17%; 4/24) reported photophobia. This is a relatively frequent symptom in patients with IRDs and is thought to reflect an early involvement of photopigment-containing cells [15,22]. It is suggested that light hypersensitivity occurs due to impairment of either S-cones in the parafoveal region, rods, and/or photosensitive retinal ganglion cells, but the mechanism is not fully understood [22].…”
Section: Disease Onsetmentioning
confidence: 99%
“…This is a relatively frequent symptom in patients with IRDs and is thought to reflect an early involvement of photopigment-containing cells [15,22]. It is suggested that light hypersensitivity occurs due to impairment of either S-cones in the parafoveal region, rods, and/or photosensitive retinal ganglion cells, but the mechanism is not fully understood [22]. Interestingly, a subset of DRAM2 patients (12%; 3/24) described difficulty seeing in dark environments and dark adaption difficulties as their initial symptoms, suggesting an early rod impairment [14,16].…”
Section: Disease Onsetmentioning
confidence: 99%
“…Retinal imaging using visible light is often associated with considerable discomfort glare 31 , 32 . Photophobia increases with decreasing wavelength, and it was therefore expected that R-AF would be better tolerated 6 , 7 .…”
Section: Discussionmentioning
confidence: 99%